FACTORS ASSOCIATED WITH THERAPEUTIC NON-ADHERENCE AMONG HYPERTENSIVE INDIVIDUALS WHO SEEK EMERGENCY CARE - Ferreira, Patrícia Chatalov; Teston, Elen Ferraz; Carvalho, Brígida Gimenez; Silva, Joice Lourenço da; Reis, Pamela dos; Rossi, Robson Marcelo; Marcon, Sonia Silva (Cogitare Enfermagem, 2023)
Objective: to analyze factors associated with therapeutic non-adherence among individuals with Arterial Hypertension who seek emergency care and/or assistance due to hypertensive complications. Method: this is a cross-sectional study conducted from December 2019 to October 2020 with 238 people living in a medium-sized municipality from southern Brazil using Morisky’s 8-Item Medication Adherence Scale. Multiple Logistic Regression was used in the analysis. Results: a total of 86 (36.1%) participants were considered as non-adherent. A higher change of non-adherence was observed in people younger than 60 years of age (Odds Ratio=2.04), who sought emergency services in the three years under study (Odds Ratio=5.08), and who had a bond with Primary Health Care professionals (Odds Ratio=1.96). Conclusion: acknowledging the factors associated with non-adherence to the therapy will allow professionals to conduct educational interventions and assist people with hypertension according to their needs, thus preventing/postponing complications.